Development of a Healthy Workplace Monitoring System using IoT Technology - Asılahtul Afrına Samsudın; Norharyati Harum; Nur Atikah Arbain; Erman Hamid (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2023)
Chronic respiratory symptoms such as long-lasting cough, wheezing, shortness of breath, and chest pain are symptoms of respiratory problems mainly developed due to occupational exposures. Occupational disease is primarily produced by the air of the factories polluted by poisonous gases, fumes and dust emanating from the manufacturing processes. An unhealthy environment will affect the worker's productivity, leading to low productivity in the workplace. In this work, we have developed a monitoring system to monitor air pollution in a workspace. The developed system is designed with a smart alert system that can help workspace management to receive a notification when the workspace is in bad air pollution conditions. The system is developed using the Rapid Application Development model by considering three-layer Internet-of-Things Architecture. The system is equipped with sensors and Arduino in the device layer, Wi-Fi in the network layer, and a cloud platform in the application layer. The developed prototype is verified through functional tests, gas detection and cloud integration.